Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41433-021-01725-5
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the therapeutic potential of IL-33 for atrophic AMD

Abstract: Age-related macular degeneration (AMD), a degenerative disease affecting the retinal pigment epithelium (RPE) and photoreceptors in the macula, is the leading cause of central blindness in the elderly. AMD progresses to advanced stages of the disease, atrophic AMD (aAMD), or in 15% of cases “wet” or neovascular AMD (nAMD), associated with substantial vision loss. Whilst there has been advancement in therapies treating nAMD, to date, there are no licenced effective treatments for the 85% affected by aAMD, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 94 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…79,80 When the long-term struggle between pro-and anti-inflammatory responses ultimately loses balance, AMD occurs. 81 In addition, innate immune cells such as macrophages, microglias, dendritic cells, and neutrophils are closely associated with the development of AMD, [82][83][84][85] but whether adaptive immunity has a role in AMD is highly debated. 86 Inflammatory responses contribute to both dry and wet AMD through different mechanisms.…”
Section: Inflammation and Amdmentioning
confidence: 99%
“…79,80 When the long-term struggle between pro-and anti-inflammatory responses ultimately loses balance, AMD occurs. 81 In addition, innate immune cells such as macrophages, microglias, dendritic cells, and neutrophils are closely associated with the development of AMD, [82][83][84][85] but whether adaptive immunity has a role in AMD is highly debated. 86 Inflammatory responses contribute to both dry and wet AMD through different mechanisms.…”
Section: Inflammation and Amdmentioning
confidence: 99%
“…Choroidal mast cells, with their unique position in the choroid and their dynamic release of bioactive mediators, are likely active participants in the progression of inflammatory and degenerative conditions [ 12 , 26 ]. Other studies further solidify this viewpoint by elucidating the mast cell’s potential in exacerbating oxidative stress, inflammation, and cellular damage in the ocular environment [ 27 , 36 , 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clare et al [ 36 ] reported that mast cell activity contributes to the pathogenesis of retinal diseases by promoting inflammation and oxidative stress. They found that mast cells can be activated by oxidative stress, leading to the release of pro-inflammatory mediators.…”
Section: Choroidal Mast Cells and Amdmentioning
confidence: 99%
“…IL-33 is an innate immunomodulatory cytokine that belongs to the IL-1 cytokine family and resides within the nuclei of various cell types ( Clare et al, 2021 ; Liew et al, 2016 ; Schmitz et al, 2005 ). Under cellular and tissue homeostasis, endogenous IL-33 negatively affects gene transcription as a nuclear protein in an intracrine fashion by sequestration of NF-κB, leading to the repression of gene expression to dampen pro-inflammatory pathways ( Martin and Martin, 2016 ; Ali et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%